Patience pays off – corporate social responsibility and long-term stock returns. (3rd April 2018) - Dorfleitner, Gregor; Utz, Sebastian; Wimmer, Maximilian
ABSTRACT: This paper presents new evidence on the implications of corporate social responsibility (CSR) on stock returns. By implementing a long-term focus as well as using subdivided measures for CSR, we cater to the intangible nature and the heterogeneity of CSR activities. We use a novel classification of these activities into nine areas, each belonging to one of the standard environment, social, and governance (ESG) dimensions. Using cross-sectional return regressions and buy-and-hold abnormal returns, we find that firms with strong CSR significantly outperform firms with weak CSR in the mid and long run in certain areas. Firm returns increase up to 3.8% with respect to a one-standard-deviation increase of the CSR rating. In a two-stage least squares (2SLS) approach we verify that the main economic channel for the appreciation of strong CSR stocks is unexpected additional cash flows. The results are relevant for assessing the efficiency of CSR, and have broader implications for asset managers who can expect abnormal returns by investing in firms that exhibit a high CSR in the respective scores and holding the stocks for a longer period.